Chemical Control of the Grape Vine Bud Mite, Eriophyes vitis (Pagenstecher) - De Klerk, C. A. (South African Journal of Enology and Viticulture, 2017)
Various chemicals were tested in field trials for the control of the grape vine bud mite. Chlorobenzilate (Akar) 50% ec at 50 ml/100 i water and propoxur (Unden) 20 % ec at 125 ml/100 i water resulted in satisfactory control. The best results were obtained with three applications per season at 14 day intervals, starting at bud burst. At least 500 ml spray mixture per vine must be applied.